Profiling the effects of pre-season on cardiovascular and sprinting performance among elite youth football players - Madarsa, N. I.; Mohamad, N. I. (Journal of Physical Education and Sport, 2022)
Football is one of the most popular team sports and is played globally by all levels and age groups. Amateur, professional, and elite groups can be differentiated by the preparation of the team. The preparation for a challenging and competitive football league needs to be planned thoroughly to ensure the players can perform at their maximum. The manipulation of a training program to suit the match demands is crucial to developing and achieving maximum performance. Thus, this study aimed to determine elite youth football players' cardiovascular fitness and sprinting performance after undergoing a six-week intensive pre-season training program that had been tailored to the demands of a match. Perak II elite youth football players (n=24, age=23.29 ± 3.02) participated in this study. The Yoyo Intermittent Recovery Test Level 2 (YYIR2) protocol determined their cardiovascular fitness performance and a 20m sprint test was used to determine their sprinting performance. Data analysed using a Paired Sample T-Test showed a significant improvement in cardiovascular fitness performance (pre-test 58.20 ± 3.10 ml•kg-1•min-1, post-test 67.73 ± 4.41 ml•kg-1•min-1) and sprinting ability performance (pre-test 3.16 ± 0.15 sec, post-test 3.09 ± 0.12 sec). In conclusion, the results indicated that the six-week pre-season training program, which included aerobic, anaerobic, and resistance training, as well as technical-tactical training drills, significantly improved cardiovascular fitness and sprinting ability. The findings imply that proper pre-season training programs based on intermittent anaerobic and aerobic training can enhance professional football players` performance and an appropriate performance-monitoring program can determine the effectiveness of a pre-season program.